Optimization of Mechanical and Durability Properties of Manganese Slag Hybrid Fiber Concrete Using an L9 Orthogonal Design and Grey Relational Analysis - Feng, Li; Chee Khoon, Ng (International Information and Engineering Technology Association (IIETA), 2025)
Studies have highlighted manganese slag (MnS) mixed-fiber concrete as a construction material, in view of the effects of varying proportions of MnS, steel fibers (SF), and polypropylene fibers (PPF) on the mechanical properties and durability of C30 MnS hybrid fiber-reinforced concrete (MHFC). Using an L9 orthogonal design, ten mix ratios were tested for compressive strength, flexural strength, and chloride ion resistance at 7, 28, 56, and 91 days. A grey relational analysis (GRA) method was employed to comprehensively evaluate nine mix proportioning schemes across four curing ages. By analyzing the grey relational degrees, the optimal mix proportioning scheme was identified. Results indicated that SF had the greatest positive impact on both compressive and flexural strength, followed by MnS, while PPF had a limited effect. The optimal mix—20% MnS, 1.0% SF, and 0.5% PPF—achieved a 23% increase in compressive strength and 33% in flexural strength at 28 days. In terms of the durability of concrete in corrosive environments, the optimal performance was achieved with a mix proportion of 10% MnS, 1.0% SF, and 1.0% PPF. These findings provide guidance for optimizing MHFC and highlight the potential of industrial by-products in enhancing concrete durability. Further research is recommended to refine mix designs and assess long-term field performance.